PERANCANGAN DAN IMPLEMENTASI WEBSITE PELAYANAN STATISTIK TERPADU FROM ANYWHERE DI BPS KABUPATEN TABANAN - Ni Made Ayu Wirasih; I Ketut Gede Suhartana; Ngurah Agus Sanjaya ER (Jurnal Pengabdian Informatika, 2025)
The advancement of digital technology encourages government agencies to provide public services that are more easily accessible to the public. The Central Bureau of Statistics (BPS) of Tabanan Regency still provides data request services directly at the office, which is considered inefficient. This study aims to design and implement an integrated statistical service website that can be accessed from anywhere to enhance the effectiveness and efficiency of public service delivery. System development was carried out through several stages, including needs identification, user interface design, feature development, and system evaluation in collaboration with the BPS technical team. The implementation results show that the website is capable of providing data request services, consultations, recommendations, and statistical service information. The evaluation indicates that the system simplifies public access to BPS services without requiring physical visits to the office. This system is expected to serve as a digital public service solution that is more adaptive and responsive to user needs.